A comprehensive review on small-scale passive solar stills for desalination. Issue 1 (1st January 2021) - Ho, Zhi Yong; Bahar, Rubina; Koo, Chai Hoon
ABSTRACT: The main focus of this review is to investigate the potential of small-scale solar desalination as a viable freshwater source by comparing the performance of different types of modification on solar stills. The design factors that could provide impacts to the parameters affecting the performance in terms of distillate production have been considered. The design factors include mostly the different mechanisms of solar stills, concentration of solar power, sand thermal storage. The impacted parameters of each type of solar stills are one of the highlights of this review. The cost of production has also been explored. The purpose of this review is to enable future researchers in identifying the appropriate features to be used for designing a solar desalination system in water and energy-stressed rural regions. The minimum cost per liter of water production reported was 0.0085 USD and the maximum production reported from modified passive solar still was reported to be 11.65 L/m 2 /day with a spherical absorber. Minor addition of active elements like a small pump to the still with Fresnel absorber reported producing 12.47 L/m 2 day. For performance enhancement of passive solar stills in water and energy scarce regions, it is suggested to add Phase change material (PCM) with heat conductive particles and solar irradiation concentration through absorbers/reflectors or Fresnel lenses. HIGHLIGHTS Renewable energy based desalination methods are preferable over energy-intensive methods. For water and energy scarce regions, independent small scale passive solar stills can be a viable option. Parameters affecting the performance of a solar still include uncontrollable climatic parameters and manipulative parameters. Highly productive passive solar stills can be designed by controlling the manipulative parameters like evaporation area of the basin, tilt angle and temperature of condensation surface, thermal gain of the feedwater by thermal storage, heat transfer using fins/conductive material in the basin. The recent trends to improve passive solar stills' efficiency with cost effectiveness include usage of sunlight concentrators through refraction, addition of conductive nano particles with thermal storage and multi-staging. GRAPHICAL ABSTRACT: UF0001